1961
DOI: 10.1113/jphysiol.1961.sp006647
|View full text |Cite
|
Sign up to set email alerts
|

Drinking by nephrectomized rats injected with various substances

Abstract: Gilman (1937), experimenting on normal dogs, observed that hypertonic solutions of sodium chloride, which cause cellular dehydration, gave rise to more drinking than hypertonic solutions of urea, which do not cause loss of cell water. He concluded that thirst is due to cellular dehydration.Experiments on dogs by Holmes & Gregersen (1950a, b) in which a variety of substances were given, confirmed that osmotically effective solutes cause most drinking and by implication most thirst, and Adolph, Barker & Hoy (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
2

Year Published

1966
1966
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 17 publications
5
56
2
Order By: Relevance
“…These results do not support the earlier work of Linazasoro, Diaz, & Mendoza (1954) but tend to confirm the work of Fitzsimons (1961). A more systematic analysis of blood sodium, potassium, osmolality.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…These results do not support the earlier work of Linazasoro, Diaz, & Mendoza (1954) but tend to confirm the work of Fitzsimons (1961). A more systematic analysis of blood sodium, potassium, osmolality.…”
Section: Discussioncontrasting
confidence: 94%
“…Linazasoro, Diaz, & Mendoza (1954) reported a reduction in ad lib water drinking in nephrectomized rats which they attributed to a lack in the "sensation of thirst." Fitzsimons (1961) did not find a lack in the "sensation of thirst" and nephrectomized rats drank more water than normal animals following intravenous injections of hypertonic solutions. Because of the particular experimental procedures which Fitzsimons (1961) employed it is difficult to compare the ad lib drinking in nephrectomized animals with normal rats.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Osmotically effective substances were therefore diluted to isotonicity by the water drunk: in this respect the iguana is comparable to the nephrectomized rat (Fitzsimons, 1961). The haematocrits and plasma [Na] levels indicated that equilibration was complete within 15 min of giving hypertonic saline.…”
Section: Pmentioning
confidence: 99%